Differences in the tests for assessment of strength and speed motor abilities between 3 generations (15, 16 and 17 years of age) boys and girls - Andonovski, Martin, Vuksanovikj, Vladimir, Aceski, Aleksandar (Faculty of Physical Education, Sport and Health - Skopje, 2020)
The objective of this research was to compare the strength and speed capacities at a sample of N=78 subjects, boys (N=42) and separately for girls (N=36) at the age of 15, 16 and 17 years, secondary school students. Three (3) tests were applied for assessment of the strength capacities and one (1) test for the speed assessment. (Push Ups-1 min, Curl Ups -1 min, Trunk Extension, Run 20meter). The results have shown that there is no significant difference between the 3 generations of boys in terms of the system of motor abilities (Wilks’ L=0.74; р=0.187; ηp 2 =0.14). Among the girls, there is significant difference between the three generations at level (Wilks’ L = 0.497; р=0.01; ηp 2 =0.295). Post-hoc tests of the girls have shown difference in the Curl Ups-1 min tests (р=0.003) between the generations first and second year generations, and Run 20 meter between the girls of first and second year (р=0.004), as well as between the girls of second and third year (р=0.002). It can be concluded that there are differences between the three generations of girls; however, we are unable to confirm with certainty the cause for such differences. It can be established with certainty that the sample of subjects presents lower values at the applied tests compared to a similar population. The recommendations of the authors refer to the following: need for correction in the curricula and the number of weekly classes in physical education in the secondary schools; increased motivation for physical activity among this population of young boys and girls, both on and outside of class activities; monitoring of the motor abilities among the youth in the Republic of North Macedonia; application of similar tests in other schools, comparison of results, development of a national strategy with instructions for development and maintenance of motor abilities among the youth.
Keywords: motor performances, youth, strength development, physical assessment, comparison